MakhtÅ«á¹ah Qaá¹£idah li al-á¹¢ibyÄn li al-Shaikh á¹¢Älih Tsaniy: Philological Study [The Manuscript of Qaá¹£idah li al-á¹¢ibyÄn by Sheikh á¹¢Älih Tsaniy: A Philological Study] - Khoir, Muhammad Wildan; Islam, M Adib Misbachul; Farhanah, Titi; Nugraha, Mugy (OKARA: Jurnal Bahasa dan Sastra, 2025)
Qasidah li al-Shibyan, a theological poem by Syaikh Sholih Tsaniy preserved within the Indonesian Islamic manuscript tradition, has not previously undergone critical editing (tahqiq) or scholarly examination. Existing studies on the author’s works have primarily focused on Qasidah fi al-Shaum, leaving his theological writings largely unexplored. This study aims to produce a critical edition of Qasidah li al-Shibyan, identify and correct scribal errors, and examine the text's theological teachings. Employing a philological approach, the research involved manuscript identification, inventory, description, comparison, and textual criticism of two digitized manuscripts (DS 0097 00052 and DS 0097 00058) preserved at the Qomaruddin Institute, Gresik. The comparative analysis revealed various orthographic and scribal variations, particularly inconsistencies in hamzah usage and the substitution of ta’ marbutah with haa’. These variants reflect common practices in Arabic manuscript transmission rather than substantive differences in meaning or doctrine. Based on textual quality and completeness, Manuscript A was selected as the base text for the critical edition. The findings demonstrate that the qasidah primarily expounds the fifty tenets of Islamic faith (‘Aqa’id al-Khamsin), encompassing the obligatory, impossible, and permissible attributes of God and His messengers. This study provides the first critical edition of Qasidah li al-Shibyan and offers new insights into the transmission of Sunni theological teachings, manuscript culture, and Islamic intellectual traditions in the Indonesian archipelago.